INFLUENCE OF INTEGRATED WEED MANAGEMENT PRACTICES AND BIOFERTILIZERS ON NODULATION OF KHARIF SOYBEAN [Glycine max (L.) Merill] - S. A HUSSAIN, CH. BHARAT BHUSHAN RAO and (The Journal of Research, PJTSAU, 2019)
Soybean [Glycine max (L.) Merill] occupies third place among oilseed crops of Telangana State and is a rich source of protein (40-42 %) and quality oil (20-22%). Presently about 90% of the area cultivated under soybean is treated with herbicides (Peer et al., 2013). The herbicides apprehend to have direct or indirect consequences on non-targeted organisms including soil micro flora in the field. Nodulation is a unique property of the legumes to fix atmospheric nitrogen and benefit the crop. Herbicide application in super optimal concentrations or applied continuously may accumulate in toxic concentrations. They pose a threat by damaging the number and weight of nodules. Niewiadomska (2004) also reported that the herbicides may directly affect the free living populations of nodular bacteria in the soil or indirectly influence the extent of infection and thus the number of nodules formed Jha et al. (2014). Singh (2007) also recorded significant improvement in number of nodules plant-1 by the combined application of Rhizobium and Pseudomonas with 5 t ha-1 FYM over the recommended dose of fertilizers.